Influence of promotion and word of mouth on purchasing decisions (a case study of Toko Family Cilacap consumers) - Umi Nur Khasanah (Digital Business: Tren Bisnis Masa Depan, 2023)
The purpose of this study was to analyze the effect of word of mouth on purchasing decisions (case study at the Cilacap Family Shop). The number of samples in this study were 75 respondents using the incidental sampling method. This study uses multiple linear regression analysis methods. The results showed that there was a simultaneous influence on variables (promotion and word of mouth) on purchasing decisions, seen significant values below 0.05 and calculated F value (63.522) ˃ F table (3.12). The results of this study also show the value of t count on the promotion variable of (3.557), word of mouth amounting to (4.302) is greater than t table (1.993) so that it is stated that the purchase results are stated. In the determination test there is an effect of 62.8% of the independent variables (promotion and word of mouth) on the dependent variable (purchasing decisions). While as much as 37.2% are considered by other variables and are not included in this regression analysis, such as location, price, brand image, brand equity, product quality and others.